IMPLEMENTASI IDS MENGGUNAKAN SNORT PADA SISTEM OPERASI UBUNTU: Implementasi IDS Menggunakan Snort Pada Sistem Operasi Ubuntu - I Putu Agus Eka Pratama; NI Kade Mega Handayani (Jurnal Mantik, 2019)
Network security can be improved by implementing the Intrusion Detection System (IDS). Snort is an Intrusion Detection System program, which is a program that can detect an intrusion attempt on a computer network system. Implementation of an Open Source intrusion based Snort detection system is a cost advantage with reliable performance in detecting attacks. Snort can be implemented on various operating systems including Ubuntu Linux. An attack can be detected or not by Snort IDS, depending on the rules / rules in Snort. Snort testing is done with several attack patterns such as Ping, Port Scanning, Ping of Deatch with several tools such as NMAP, SQLMAP and others. Based on the results of testing Snort can detect and provide warnings about attacks that threaten a computer network of a server. The test results are expected to be used as a alternative in server network security.